Association of Cumulative Dose of Haloperidol With Next-Day Delirium in Older Medical ICU Patients*. Issue 5 (May 2015) - Pisani, Margaret A.; Araujo, Katy L. B.; Murphy, Terrence E.
<x xml:space="preserve">Abstract</x> Objectives: To evaluate the association between cumulative dose of haloperidol and next-day diagnosis of delirium in a cohort of older medical ICU patients, with adjustment for its time-dependent confounding with fentanyl and intubation. Design: Prospective, observational study. Setting: Medical ICU at an urban, academic medical center. Patients: Age 60 years and older admitted to the medical ICU who received at least one dose of haloperidol (n = 93). Of these, 72 patients were intubated at some point in their medical ICU stay, whereas 21 were never intubated. Interventions: None. Measurements and Main Results: Detailed data were collected concerning time, dosage, route of administration of all medications, as well as for important clinical covariates, and daily status of intubation and delirium using the confusion assessment method for the ICU and a chart-based algorithm. Among nonintubated patients, and after adjustment for time-dependent confounding and important covariates, each additional cumulative milligram of haloperidol was associated with 5% higher odds of next-day delirium with odds ratio of 1.05 (credible interval [CI], 1.02–1.09). After adjustment for time-dependent confounding and covariates, intubation was associated with a five-fold increase in odds of next-day delirium with odds ratio of 5.66 (CI, 2.70–12.02). Cumulative dose of haloperidol among intubated patients did not change their already high likelihood of next-day delirium. After adjustment for time-dependent confounding, the positive associations between indicators of intubation and of cognitive impairment and next-day delirium became stronger. Conclusions: These results emphasize the need for more studies regarding the efficacy of haloperidol for treatment of delirium among older medical ICU patients and demonstrate the value of assessing nonintubated patients.